Can religion (un)zombify? The trajectories of psychic capture theology in postcolonial South Africa - Dube, Bekithemba (HTS teologiese studies, 2020)
‘Police arrested suspected criminals in a satanic place masquerading as a church … There is no church there, but there is Satanism … Those people are not praying for anything, but they have hypnotised abantu [people]’. Informed by a decoloniality lens in relation to motifs such as coloniality of power and knowledge and being, I argue that mafiarised religions in South Africa thrive through psychic capture theology. Some emerging religious movements subject their followers to unthinkable practices, which makes outsiders question the way in which both religious leaders and adherents operate outside the conventionally accepted practice of religion, and, instead, indulge in practices characterised by manipulation, corruption and mental destabilisation. I respond to two questions: What are the trajectories of a religion that zombifies, and how can the social pathologies of psychic capture theology be addressed? I respond to these questions with special reference to the Seven Angels Ministry and Penuel Mnguni. I argue that some emerging ministries strive to destroy the psychic ability of adherents, to achieve strategic distance that dehumanises, removes people from the zone of being, and causes them to question their ontological density. I end the article by arguing that there is a need for religion to be regulated, and reintroduced, to challenge religious mafias that thrive through mental destabilisation. In doing so, religion can be reconfigured and have relevance in a postcolonial state, such as South Africa, especially in contexts where the rationale of religious discourses is questionable.Contribution: The article contributes to knowledge in the sense that it calls for religion to be problematised and reconstructed within education and sociological space when it dehumanise and removes people from the zone of being. Through this approach, the article fits with the scope for the journal that calls for interdisciplinary approach to the study within the international contexts.